EFEKTIVITAS MEDIA AUDIO-TAKTIL DALAM PEMBELAJARAN PAI UNTUK ANAK TUNANETRA - Devi Khusuma Najwa; Ulin Ahmad Saputro; Denisa Ria Hikmah; Hidayatu Munawaroh (CV. Lafadz Jaya, 2026)
Abstract This study aims to examine the effectiveness of audio-tactile media in Islamic Religious Education (PAI) learning for visually impaired students, who have long been constrained by the dominance of visually-based instructional media. A quantitative approach was employed using a quasi-experimental method with a nonequivalent control group design, involving an experimental group using audio-tactile media and a control group receiving conventional instruction. Data were collected through pre-test, post-test, observation, and documentation, then analyzed using inferential t-test statistics. The results revealed a significant difference between the two groups; the experimental group demonstrated greater learning achievement gains alongside more active, interactive, and inclusive learning processes through integrated auditory and tactile stimulation. Therefore, audio-tactile media is proven to be effective and applicable in PAI learning for visually impaired children.